Pengaruh Pelatihan Manajemen Stres untuk Menurunkan Tingkat Stres pada Orang dengan Diabetes Mellitus Tipe 2 - Difni Sepnida Effendi (Jurnal Psikologi, 2020)
This study aims to determine differences in stress levels in people with type 2 diabetes mellitus before and after being given treatment for the Stress Management Training intervention. The design used in this study is one group pretest-posttest design. Subjects in this study were people with type 2 diabetes mellitus male and female, aged 40-60 years, had a stress score with moderate to high stress levels, had a minimum high school education. Stress is measured using a stress scale of 39 items. Subjects in this study amounted to 5 people. Subjects were given treatment in the form of a Stress Management Training intervention which was a combination of knowledge and training skills in the form of mindfulness and positive thinking. Quantitative data analysis techniques using Wilcoxon sign rank analysis is to find out whether there is a difference in stress scores between pretest and posttest and posttest and follow-up on the research subjects. Qualitative data analysis from the results of observations, interviews, worksheets and evaluation sheets. The results of this study indicate that there are significant differences between stress scores before treatment with stress scores after being given treatment of the Stress Management Training intervention. Based on the quantitative results the Wilcoxon sign rank test shows that in this study there were significant differences between pretest and posttest with Z = -2.023ͣ (p <0.050). The results of the study can also be seen from the decrease in the mean score between pretest and posttest. Pretest with mean scores (= 92.20) and posttest with mean scores (= 76.60). The mean posttest value is lower than the pretest mean value. This means that there is a decrease in the score on the pretest mean to the posttest. Based on the explanation above it can be concluded that stress management training can reduce stress in people with type 2 diabetes mellitus.